Zinc electrode with high utilization rate and high stability, preparation method and application
Patent Information
- Application Number
- CN202510101266.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-22
AI Technical Summary
Under high-deep discharge conditions, the cycle life of the zinc powder electrode is limited and polarization is prone to occur, resulting in low utilization rate of zinc electrodes and insufficient energy density, limiting the commercial development of zinc-based batteries.
By reasonably adjusting the composite composition and structure of zinc powder, low viscosity oxygen-containing polymers are used as binders and spherical carbon materials as functional additives to form functional coatings to enhance the rapid migration and electrochemical-mechanical properties of zinc ions.
The long cycle life of zinc powder negative electrode of zinc-based energy storage devices under high-deep discharge conditions has been achieved, the utilization rate of zinc metal and the overall energy density of the battery has been improved, and the practical development of zinc-based energy storage has been promoted.
Smart Images

Figure CN119650562A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of zinc metal electrodes for aqueous zinc ion batteries, and more specifically to a high-utilization and high-stability zinc electrode and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy sources such as wind and solar energy, electrochemical energy storage technology is playing an increasingly vital role. Electrochemical energy storage can efficiently regulate the storage and transmission of electrical energy, ensuring the safe and smooth transmission of electrical energy. It not only has broad application prospects in large-scale power grid systems, but also gradually penetrates into green transportation, household and industrial fields. Among various electrochemical energy storage technologies, aqueous zinc-ion batteries have strong competitiveness in high-safety applications such as large-scale energy storage and household use due to their inherent high safety, rich zinc resources, and low cost.
[0003] Achieving stable cycling performance of zinc metal electrodes under high depth of discharging (DOD) conditions remains a major challenge, severely limiting the commercial development of zinc-based batteries. Currently, the materials widely used as zinc metal electrodes are mainly zinc foil and zinc powder. However, the thickness of zinc foil in industrial production is relatively thick, usually between 100 and 300 μm, resulting in excessive mass loading of zinc in the zinc electrode, which leads to low utilization of zinc metal in battery devices and negatively affects the overall energy density of the battery. In recent years, zinc powder has been considered as a promising zinc metal anode material. Zinc powder has similar low-cost advantages to zinc foil, while also having convenient callable amounts, which is conducive to improving zinc metal utilization. However, the cycle life of zinc powder electrodes is still limited under high DOD, and when the DOD exceeds 15%, it usually lasts less than 400 hours (EnergyStorage Materials, 2025, 74, 103934). At high DOD, zinc powder electrodes exhibit significant polarization. This is because the zinc ion transfer kinetics, corrosion reactions, and stress problems associated with zinc powder electrodes are more severe under high DOD conditions. In order to achieve long cycle performance under high DOD, a new electrode structure design is required to fully regulate the electrochemical-mechanical properties of zinc powder.
[0004] Therefore, it is necessary to provide a high-utilization and high-stability zinc electrode and its preparation method and application to adjust the electrochemical and mechanical properties of zinc powder and alleviate the electrode stress cracking problem caused by the volume stress of the zinc electrode. Summary of the invention
[0005] The purpose of the present invention is to provide a high-utilization and high-stability zinc electrode and its preparation method and application. The present invention reasonably adjusts the composite composition and structure of zinc powder to achieve rapid migration of zinc ions, lock free water molecules, and relieve stress concentration, thereby enhancing the long cycle life of the zinc powder negative electrode of the zinc-based energy storage device under high DOD, achieving the construction of a zinc-based battery with a high-utilization and high-stability zinc metal negative electrode and a low negative electrode capacity / positive electrode capacity ratio (N / P ratio), and promoting the practical development of zinc-based energy storage.
[0006] To achieve the above object, the technical solution of the present invention is as follows: In one aspect, the present invention provides a high-utilization and high-stability zinc electrode, comprising a substrate and a functional coating attached to the surface of the substrate.
[0007] Furthermore, the thickness of the substrate and the coating is 1:(0.1~0.5).
[0008] Furthermore, the substrate is carbon paper, carbon cloth, copper mesh or copper foil.
[0009] Furthermore, the functional coating comprises zinc powder, a binder and a functional additive.
[0010] Furthermore, the adhesive is a polymer molecule with a room temperature viscosity of less than 1000 Pa.S. In the present invention, the room temperature condition is 10-40°C, preferably 15-35°C.
[0011] Furthermore, the adhesive is at least one of random polyether, polyether polyol or polyethylene glycol.
[0012] Furthermore, the adhesive is selected from at least one of glycerol random polyether, elastomer polyether polyol or polyethylene glycol.
[0013] Furthermore, the random polyether is selected from at least one of isomeric tridecanol random polyether, propylene glycol random polyether, glycerol random polyether, butanetriol random polyether, lauric acid random polyether and dodecanol random polyether.
[0014] Furthermore, the glycerol random polyether may be glycerol random polyether 3000.
[0015] Furthermore, the polyethylene glycol may be polyethylene glycol 200, polyethylene glycol 400 or polyethylene glycol 600.
[0016] Furthermore, the functional additive is preferably a spherical carbon material.
[0017] Furthermore, the functional additive is selected from at least one of nano carbon black, fullerene, activated carbon, and carbon microspheres.
[0018] Furthermore, the mass ratio of the zinc powder, the binder and the functional additive is (0.5-2):(0.3-0.8):(0.5-2), preferably 1:0.6:1.
[0019] In one aspect, the present invention provides a method for preparing a zinc electrode, comprising the following specific steps: S1: mixing zinc powder, binder and functional additives with solvent to form slurry; S2: applying the slurry to the surface of the current collector substrate and drying to form a functional coating; S3: After drying, cut into electrode sheets to obtain zinc electrodes.
[0020] Furthermore, the solvent is selected from at least one of ethanol, methanol and water.
[0021] Furthermore, the mixing can be carried out in a mixer or by ultrasonic dispersion.
[0022] Furthermore, the mixing is carried out in a mixer, the mixer speed is 5-20 rpm, and the stirring time is 2-10 hours.
[0023] Furthermore, the mixing is carried out by ultrasonic dispersion, the ultrasonic power is 50-100 W, and the ultrasonic time is 5-40 min.
[0024] Furthermore, the substrate of the current collector is carbon paper, carbon cloth, copper mesh, copper foil, etc.
[0025] Furthermore, the drying temperature is 60-100° C. and the drying time is 1-10 hours.
[0026] In one aspect, the present invention provides a zinc-containing battery or a zinc-based energy storage device, comprising the zinc electrode of the present invention. Further, the zinc-containing battery or zinc-based energy storage device is a low N / P zinc-based battery.
[0027] On the other hand, the present invention provides a use of the zinc electrode of the present invention in preparing a zinc-containing battery or a zinc-based energy storage device.
[0028] Compared with the prior art, the beneficial technical effects of the present invention are as follows: 1. The present invention provides a high-utilization and high-stability zinc electrode; the zinc electrode has excellent zinc ion conductivity, can effectively inhibit zinc metal corrosion induced by free water, and can alleviate the problem of electrode stress cracking caused by the volume effect of the zinc electrode ( Figure 1 It can be seen that there is no cracking phenomenon; Figure 2 It can be seen that the components are highly uniform), and can be used as zinc metal electrodes for various zinc-based energy storage devices.
[0029] 2. The present invention provides a method for preparing a high-utilization and high-stability zinc electrode; the method comprises mixing zinc powder, a low-viscosity oxygen-containing polymer binder and a functional carbon material additive with a simple solvent, and then coating the mixture on a current collector, and then cutting and forming the mixture after drying to obtain a high-utilization and high-stability zinc electrode, which overcomes the shortcomings of the prior art and can achieve stable cycle performance of the zinc electrode at high utilization (Example 1 Figure 3 It is shown that it can be cycled for 600~1000h), which provides the possibility for the practical application of zinc-based energy storage devices in the future.
[0030] 3. Different from the previous composite technology of zinc electrode, the present invention uses low viscosity oxygen-containing polymer as binder, combined with spherical carbon material additives to enhance the ion migration kinetics during the electrochemical cycle of zinc electrode (such as Figure 3 , Figure 4 and Figure 7 ), inhibit parasitic side reactions and alleviate stress concentration (as shown in Figure 5 and 6 As shown in the figure), the electrochemical and mechanical properties of the zinc electrode are comprehensively improved.
[0031] 4. The high-utilization and high-stability zinc electrode prepared by the present invention has a simple preparation method, and the materials can directly use commercial materials. The materials used are safe, non-toxic or low-toxic, and have minimal pollution to the environment. It has significant low cost and environmental protection advantages. In addition, the loading amount of the high-utilization and high-stability zinc electrode of the present invention can be easily controlled, which is beneficial to match the positive electrode to assemble a low N / P zinc battery system and improve the overall energy density of the zinc battery.
[0032] 5. The preparation method of the present invention is green and safe, has low energy consumption, low cost, high scalability, and excellent controllability. The obtained zinc electrode can significantly improve the zinc ion diffusivity under high DOD conditions ( Figure 4 As shown in the figure), parasitic side reactions induced by free water and stress cracking caused by volume effect are suppressed, and the long-cycle stability under high zinc metal utilization (15-96%) is prolonged, showing good application prospects in low N / P zinc-based devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a physical photo of the high-utilization and high-stability zinc electrode prepared in Example 1 of the present invention.
[0034] Figure 2 This is the scanning electron microscope surface morphology of the high-utilization and high-stability zinc electrode prepared in Example 1.
[0035] Figure 3The cycle performance of the symmetrical battery assembled based on the zinc electrode prepared in Example 1 at high utilization (15%). In the figure, GPE-CB-ZnP is a high utilization and high stability zinc electrode, and the control group is a zinc electrode composited with a conventional PVDF binder. PVDF is a high viscosity polymer.
[0036] Figure 4 The cycling performance of a symmetrical battery assembled based on the zinc electrode prepared in Example 1 at an ultra-high utilization rate (96%).
[0037] Figure 5 The morphology of GPE-CB-ZnP and conventional PVDF binder zinc anode after cycling at high utilization rate.
[0038] Figure 6 The zinc electrode prepared in Example 1 and Zn 0.25 V 2 O 5 The cycling performance of the full battery assembled by positive electrode matching under low N / P conditions; the test conditions are: after the battery is assembled, it is left to stand for 6 hours before starting the charge and discharge cycle, and the current density is 0.1A g -1 .
[0039] Figure 7 The impedance and ion migration coefficient of GPE-CB-ZnP and conventional PVDF binder zinc anode DETAILED DESCRIPTION
[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0041] The reagents used in the present invention can be purchased from the market or prepared by the method described in the present invention.
[0042] The technical solution of the present invention is illustrated below by way of example, and the scope of protection requested by the present invention includes but is not limited to the following embodiments.
[0043] Example 1 (1) Weigh 1 g of zinc powder, 0.6 g of carbon black, and 1 g of propylene glycol random polyether, add 1 mL of ethanol, and grind evenly; (2) The mixture obtained in step (1) was subjected to ultrasound (ultrasound power of 80 W) for 30 min to fully mix the components.
[0044] (3) The slurry obtained in step (2) was coated on a carbon paper current collector and dried in an oven at 60 degrees for 2 h.
[0045] Figure 1 This is a real photo of the high-utilization and high-stability zinc electrode prepared in Example 1; Figure 1 It can be seen that the surface of the obtained zinc electrode is uniform and there is no cracking. Figure 2 The scanning electron microscope surface morphology of the high utilization rate and high stability zinc electrode prepared in Example 1; Figure 2 It can be seen that the obtained zinc electrode zinc powder and other components are highly uniformly composited.
[0046] Figure 3 The cycling performance of the Zn|Zn symmetric battery based on the zinc electrode prepared in Example 1 is shown in FIG. Figure 3 It can be seen that the Zn‖Zn symmetric battery based on high-utilization and high-stability zinc electrode has excellent long-cycle performance (600-1000 h) at high utilization. In contrast, the high-viscosity PVDF composite zinc electrode system can only cycle for 50 h.
[0047] Figure 4 The cycle performance of the Zn|Zn symmetric battery based on the zinc electrode prepared in Example 1 at ultra-high utilization (96%). Figure 4 It can be seen that the Zn‖Zn symmetric battery based on high-utilization and high-stability zinc electrode can still be stably cycled for 400 h when the utilization is close to 100%.
[0048] Figure 5 The morphology of GPE-CB-ZnP and conventional PVDF binder zinc anode after cycling at high utilization. Figure 5 It can be seen that the morphology of GPE-CB-ZnP after cycling has good integrity, and the PVDF binder zinc negative electrode exhibits electrode cracking after cycling.
[0049] Figure 6 The zinc electrode prepared in Example 1 and Zn 0.25 V 2 O 5 The positive electrode matches the cycle performance of the assembled full battery under low N / P conditions. Figure 5 It can be seen that under low N / P conditions, the full battery can be cycled stably for 200 h and maintain an extremely high capacity retention rate (above 90%).
[0050] Figure 7 The impedance and ion migration number of GPE-CB-ZnP and conventional PVDF binder zinc anode. Figure 7 It can be seen that the impedance of GPE-CB-ZnP and conventional PVDF binder zinc negative electrode, according to the impedance calculated corresponding ion migration number GPE-CB-ZnP is higher.
[0051] Example 2 (1) Weigh 1 g of zinc powder, 0.6 g of carbon black, and 1 g of polyethylene glycol 400, add 1 mL of ethanol, and grind evenly; (2) The mixture obtained in step (1) was subjected to ultrasound (ultrasound power of 100 W) for 40 min to fully mix the components.
[0052] (3) The slurry obtained in step (2) was coated on the copper mesh current collector and placed in an oven at 80 degrees to dry for 1 h.
[0053] Example 3 (1) Weigh 1 g of zinc powder, 0.6 g of carbon black, and 1 g of propylene glycol random polyether, add 1 mL of ultrapure water, and grind evenly; (2) The mixture obtained in step (1) was subjected to ultrasound (ultrasound power of 100 W) for 30 min to fully mix the components.
[0054] (3) The slurry obtained in step (2) was coated on a carbon paper current collector and dried in an oven at 100 degrees for 1 hour.
[0055] Example 4 (1) Weigh 1 g of zinc powder, 0.6 g of carbon black, and 1 g of propylene glycol random polyether, add 1 mL of ultrapure water, and grind evenly; (2) The mixture obtained in step (1) was mixed uniformly in a mixer at a speed of 15 rpm for 3 h to ensure that the components were fully mixed.
[0056] (3) The slurry obtained in step (2) was coated on a carbon paper current collector and dried in an oven at 100 degrees for 1 hour.
[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-utilization and high-stability zinc electrode, characterized in that: It comprises a substrate and a functional coating attached to the surface of the substrate, wherein the functional coating comprises zinc powder, a binder and a functional additive; The adhesive is a polymer molecule with a room temperature viscosity of less than 1000 Pa.S.
2. The high-utilization and high-stability zinc electrode according to claim 1, characterized in that: The adhesive is at least one of random polyether, polyether polyol or polyethylene glycol; The functional additive is preferably a spherical carbon material.
3. The high-utilization and high-stability zinc electrode according to claim 2, characterized in that: The adhesive is selected from at least one of glycerol random polyether, elastomer polyether polyol or polyethylene glycol, and the random polyether is selected from at least one of isomeric tridecanol random polyether, propylene glycol random polyether, glycerol random polyether, butanetriol random polyether, lauric acid random polyether and dodecanol random polyether; The glycerol random polyether is glycerol random polyether 3000; The polyethylene glycol is polyethylene glycol 200, polyethylene glycol 400 or polyethylene glycol 600.
4. The high-utilization and high-stability zinc electrode according to claim 2, characterized in that: The functional additive is selected from at least one of nano carbon black, fullerene, activated carbon and carbon microspheres.
5. The high-utilization and high-stability zinc electrode according to claim 2, characterized in that: The mass ratio of the zinc powder, the binder and the functional additive is (0.5-2): (0.3-0.8): (0.5-2).
6. A method for preparing the zinc electrode according to claim 1, characterized in that: The specific steps include: S1: mixing zinc powder, binder and functional additives with solvent to form slurry; S2: applying the slurry to the surface of the current collector substrate and drying to form a functional coating; S3: After drying, cut into electrode sheets to obtain zinc electrodes.
7. The preparation method according to claim 6, characterized in that: The solvent is selected from at least one of ethanol, methanol and water; The mixing is uniformly mixing in a mixer or dispersing by ultrasound; The substrate of the current collector is carbon paper, carbon cloth, copper mesh or copper foil.
8. The preparation method according to claim 6, characterized in that: The mixing is carried out in a mixer, the mixer speed is 5-20 rpm, and the stirring time is 2-10 hours; The mixing is carried out by ultrasonic dispersion, the ultrasonic power is 50-100 W, and the ultrasonic time is 5-40 min; The drying temperature is 60-100° C. and the drying time is 1-10 hours.
9. A zinc-containing battery or a zinc-based energy storage device, comprising the zinc electrode according to any one of claims 1 to 5 or the zinc electrode prepared by the method according to any one of claims 6 to 8; further preferably, the zinc-containing battery or zinc-based energy storage device is a low N / P zinc-based battery.
10. Use of the zinc electrode according to any one of claims 1 to 5 or the zinc electrode prepared by the method according to any one of claims 6 to 8 in preparing a zinc-containing battery or a zinc-based energy storage device; further preferably, the zinc-containing battery or zinc-based energy storage device is a low N / P zinc-based battery.
Citation Information
Patent Citations
Plastic soft solid zinc powder compound negative electrode material as well as preparation method and application thereof
CN116314680A
Viscoelastic soft solid electrolyte and preparation method and application thereof
CN117832651A
Electrodes for energy storage device comprising novel binders
WO2024086621A2